The Effect of Cake Application Supported by Self-directed Learning on The Students’ Speaking Skills at Junior High School - Ratnasari; Saiful; Dewi, Ratna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aimed to investigate the effectiveness of the Cake Application supported by Self-Directed Learning (SDL) in enhancing students’ speaking skills at SMP Negeri 3 Galesong Selatan. A quantitative research design with a quasi-experimental approach was used. Data was collected through pre-test and post-test assessments, with a population of 135 eighth-grade students across six classes in the academic year 2024/2025. The sample consisted of two classes, the experimental class (VIII C) and the control class (VIII D), each with 20 students. The study found that the Cake Application supported by Self-Directed Learning (SDL) significantly enhanced students' speaking skills, with the experimental group showing a larger increase in mean scores (68.67) compared to the control group (62.67). Statistical analysis indicated significant enhancements in both groups from the Pre-Test to the Post-Test, with the experimental group demonstrating a more substantial change (Z = -3.949, p = 0.000). Additionally, the experimental group had a higher mean rank (26.80) than the control group (14.20) in the Mann-Whitney U test (Z = -3.770, p = 0.000). with the effect size (Cohen's d ≥ 0.8) indicating a significant effect of Cake Application through Self-Directed Learning (SDL). This demonstrates that the intervention enhanced students' speaking skills more effectively than the conventional method. In conclusion, the study supports the effectiveness of the Cake Application through Self-Directed Learning in enhancing students’ speaking skills. The positive results highlight the potential for integrating this application into language education to improve academic performance and suggest its wider application in similar educational contexts.